Bioresorbable, Wireless, Passive Sensors as Temporary Implants for Monitoring Regional Body Temperature. Issue 16 (29th June 2020) - Lu, Di; Yan, Ying; Avila, Raudel; Kandela, Irawati; Stepien, Iwona; Seo, Min‐Ho; Bai, Wubin; Yang, Quansan; Li, Chenhang; Haney, Chad R.; Waters, Emily A.; MacEwan, Matthew R.; et al.
Abstract: Measurements of regional internal body temperatures can yield important information in the diagnosis of immune response‐related anomalies, for precisely managing the effects of hyperthermia and hypothermia therapies and monitoring other transient body processes such as those associated with wound healing. Current approaches rely on permanent implants that require extraction surgeries after the measurements are no longer needed. Emerging classes of bioresorbable sensors eliminate the requirements for extraction, but their use of percutaneous wires for data acquisition leads to risks for infection at the suture site. As an alternative, a battery‐free, wireless implantable device is reported here, which is constructed entirely with bioresorbable materials for monitoring regional internal body temperatures over clinically relevant timeframes. Ultimately, these devices disappear completely in the body through natural processes. In vivo demonstrations indicate stable operation as subcutaneous and intracranial implants in rat models for up to 4 days. Potential applications include monitoring of healing cascades associated with surgical wounds, recovery processes following internal injuries, and the progression of thermal therapies for various conditions. Abstract : Fully bioresorbable, wireless, battery‐free temperature sensors enable measurements of local internal body temperatures over clinically relevant timeframes and then ultimately disappear completely in the body, thereby eliminating the need for extraction surgeries. Potential applications include monitoring of processes associated with wound healing and managing the effects of hyperthermia and hypothermia therapies.